Jose Monserrat Maceda breaking music's frontiers - Santos, Ramon; Red, Jon; De la Cruz, Libertine Santos (Kuwadro., 2002)
Documents Jose Monserrat Maceda's life-long dedication to the understanding and popularization of Filipino traditional music. His compositions, like Ugma-ugma (1963), Pagsamba (1968), and Udlot-udlot, are monuments to his unflagging commitment to Philippine music. Maceda's music, researches and fieldwork enlighten the scholar, both Filipino and foreign, about the nature of Philippine traditional and ethnic music.